A construção da oficialidade naval no Império: os Estatutos de 1858 na Academia de Marinha - Luana de Amorim Donin (Navigator)
This article deals with the reform in the Naval Academy’s statutes in 1858 in order to observe the evolution of a political and military project for naval and Imperial Navy officers. Such reform matched with conservative political project of the Empire of Brazil that sought to insert the innovations of Western modernity with the traditions inherited from the colonial period. The Imperial Navy was rescued as a state administration arm and introduced himself as a space where aspects of civilization, the new understanding of the military role in the West and the scientific and technological developments of the period were experienced.